HUBUNGAN USIA DAN PEKERJAAN IBU DENGAN KEJADIAN PREEKLAMPSIA - Rubiati Hipni (Jurnal Inovasi Penelitian, 2022)
Preeclampsia is a pregnancy disorder characterized by hypertension and proteinuria occurring after 20 weeks of gestation which affects 5-7% of pregnant women worldwide and is a major cause of maternal and neonatal morbidity and mortality.The purpose of this study was to determine the relationship between age and mother's occupation of the incidence of preeclampsia at Idaman Banjarbaru Hospital. The method used was an analytic survey with the research design used was case control, using a purposive sampling technique, the respondents used in the case were 100 pregnant women with preeclampsia and in the control 100 normal pregnant women, data collection used secondary data by looking medical records were then analyzed univariately and bivariately using Rank Spearman Correlation analysis. The results of the study showed that there was a significant relationship between age and the incidence of preeclampsia (p=0.000). There was no significant relationship between maternal occupation and the incidence of preeclampsia (p=0.243). This study can be concluded that there is a significant relationship between age and the incidence of preeclampsia and there is no significant relationship between work and the incidence of preeclampsia